2019
DOI: 10.3389/fphar.2019.00943
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration of Memantine in the Cerebrospinal Fluid of Alzheimer’s Disease Patients and Its Consequence to Oxidative Stress Biomarkers

Abstract: Memantine is a noncompetitive N -methyl-d-aspartate (NMDA) receptor antagonist utilized as a palliative cure for Alzheimer’s disease. This is the second study examining the memantine concentrations in cerebrospinal fluid. The previously published study enrolled six patients, and three of them were theoretically in a steady state. In our study, we enrolled 22 patients who regularly used a standard therapeutic dose of memantine (20 mg/day, oral administration) before the sample collection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Of note, memantine reduces OP-induced cell death in various vulnerable brain regions such as the amygdala, thalamus, piriform cortex, hippocampus, and parietal cortex (Jackson et al 2019). Moreover, memantine lowers levels of oxidative stress markers in the cerebrospinal fluid, especially non-protein thiols and 3-nitrotyrosine (Valis et al 2019). Although we used the maximal recommended dose (20 mg/kg; Stojiljkovic et al 2019), memantine alone as pretreatment decreased the toxicity of soman only slightly (the protective ratio 1.18) and grants little to no effect in the efficacy of post-exposure treatment (see Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, memantine reduces OP-induced cell death in various vulnerable brain regions such as the amygdala, thalamus, piriform cortex, hippocampus, and parietal cortex (Jackson et al 2019). Moreover, memantine lowers levels of oxidative stress markers in the cerebrospinal fluid, especially non-protein thiols and 3-nitrotyrosine (Valis et al 2019). Although we used the maximal recommended dose (20 mg/kg; Stojiljkovic et al 2019), memantine alone as pretreatment decreased the toxicity of soman only slightly (the protective ratio 1.18) and grants little to no effect in the efficacy of post-exposure treatment (see Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Memantine decreases levels of advanced protein oxidation products (AOPP) and advanced glycation end products (AGEs) in patients with prediabetes and cognitive impairment [ 149 ]. In addition, memantine can decrease nitrosative stress and increase antioxidant protection of nonprotein thiols in the cerebrospinal fluid [ 150 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reason why this effect does not translate in patients remains to be understood, but it is worth noting that the proposed Memantine (Ebixa) AD treatment is 20 mg/d, which corresponds to a lower dose than those used in preclinical neuroprotection studies. Recent results indicated that Memantine levels in the cerebrospinal fluid during memantine treatment are not sufficient to trigger NMDA response ( Valis et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%